Behavior in Using Video Streaming Technology: Facilitating Conditions and Habits - Amanah, Dita; Harahap, Dedy Ansari (Politeknik Negeri Padang, 2024)
The research was motivated by the phenomenon of active Twitch users in Indonesia, both as streamers and viewers, which had decreased from the previous few years. When compared to neighboring countries such as China, Japan and Korea, Indonesia has the lowest number of total users. The decrease in the number of users has an impact on Twitch's market penetration efforts into Indonesia and for streamers from Indonesia who are building their careers on the Twitch website. Research was conducted to obtain an overview of the level of acceptance of Twitch video streaming technology in Bandung. The use of the UTAUT2 model was implemented to obtain factors influencing the level of acceptance of Twitch usage. The research method uses quantitative, namely distributing online surveys from Google Form to the population and samples using the purposive sampling method. Distributing the questionnaire via social media then collecting the data in Microsoft Excel and SPSS for data processing. The research results show that the behavior of using Twitch video streaming is influenced by facilitating conditions and habits.